Using a map-based assessment tool for the development of cost-effective WFD river basin action programmes in a changing climate. (1st August 2016) - Kaspersen, Bjarke Stoltze; Jacobsen, Torsten Vammen; Butts, Michael Brian; Jensen, Niels H.; Boegh, Eva; Seaby, Lauren Paige; Müller, Henrik Gioertz; Kjaer, Tyge
Abstract: For the 2nd and 3rd river basin management cycles (2015–2027) of the Water Framework Directive (WFD), EU Member States are required to fully integrate climate change into the process of river basin management planning (RBMP). Complying with the main WFD objective of achieving 'good ecological status' in all water bodies in Denmark requires Programmes of Measures (PoMs) to reduce nitrogen (N) pollution from point and diffuse sources. Denmark is among the world's most intensively farmed countries and in spite of thirty years of significant policy actions to reduce diffuse nutrient emissions, there is still a need for further reductions. In addition, the impacts of climate change are projected to lead to a situation where nutrient loads will have to be reduced still further in comparison to current climate conditions. There is an urgent need to address this challenge in WFD action programmes in order to develop robust and cost-effective adaptation strategies for the next WFD RBMP cycles. The aim of this paper is to demonstrate and discuss how a map-based PoMs assessment tool can support the development of adaptive and cost-effective strategies to reduce N losses in the Isefjord and Roskilde Fjord River Basin in the north east of Denmark. The tool facilitates assessments of the application of agri-environmental measures that are targeted towards low retention agricultural areas, where limited or no surface and subsurface N reduction takes place. Effects of climate change on nitrate leaching were evaluated using the dynamic agro-ecosystem model 'Daisy'. Results show that nitrate leaching rates increase by approx. 25% under current management practices. This impact outweighs the expected total N reduction effect of Baseline 2015 and the first RBMP in the case study river basin. The particular PoMs investigated in our study show that WFD N reduction targets can be achieved by targeted land use changes on approx. 4% of the agricultural area under current climate conditions and approx. 9% of the agricultural area, when projected climate change impacts on nitrate leaching rates are included in the assessment. The study highlights the potential of the PoMs assessment tool to assist in evaluation of alternative WFD RBMP scenarios to achieve spatially targeted and cost-effective reductions of N loads at catchment scale in the context of a changing climate. Highlights: A methodology for integrating climate change in river basin planning is presented. A map-based tool is used to assess climate change adaptation in WFD PoMs scenarios. Our findings indicate a significant effect of climate change on nitrate leaching. Spatial targeting of measures can achieve WFD environmental goals cost-effectively. Recommendations for adaptation to projected climate changes in RBMPs are provided.